A "década perdida" das exportaç\~oes nrasileiras de nens industrializados: Análise do período 2005-2016 - Fernando José Ribeiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The objective of this study is to analyze the performance of Brazilian exports of industrialized products in the period 2005-2016, with approaches that allow identifying some factors that characterize this process, not only at the level of industrial activity as a whole, but also in terms of the sectors of according to the National Classification of Economic Activity (CNAE) of IBGE. It is important to emphasize that it is not intended to identify the determinants of poor export performance, but to contribute to a better understanding of what happened with the country's industrial exports. In order to do this, we use disaggregated databases of Brazilian exports and world imports, for which we have carried out some exercises of dismembering exports in different ways, in order to analyze and measure the magnitude and relevance of issues such as the loss of competitiveness of the sector, the effect of relative prices and the effect of the composition of sales in terms of products and countries of destination.
Keywords: F13; F14; O25; 330; international trade; competitiveness; industrial policy